DIGITAL DOWRY IN ISLAMIC MARRIAGE LAW: A STUDY ON THE LEGITIMACY OF CRYPTO ASSETS AS DOWRY - Iksan, Hairul Muhammad; Fikri, Nur Muhammad; Mazid, Muhammad Nur; Zaini, Muhammad Irhas (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
The advancement of digital technology has led to transformations in various aspects of life, including the practice of dowry in Islamic marriage. One emerging phenomenon is the use of cryptocurrency, such as Bitcoin, as a form of dowry. This issue has sparked debates among scholars and academics regarding its validity, as crypto assets are highly volatile and lack physical form. This topic is crucial because it relates to the validity of marriage contracts, the principle of asset clarity, and the implementation of Islamic law in the digital era. This study aims to analyze the legitimacy of cryptocurrency as dowry within the framework of Islamic law and Indonesian positive law, as well as to highlight the urgency of legal regulation regarding this phenomenon. The research employs a qualitative method using a normative juridical approach through library research, examining primary sources such as the Qur’an, Hadith, the Compilation of Islamic Law (KHI), the Marriage Law, DSN-MUI Fatwa No. 144 of 2021, and BAPPEBTI regulations on crypto assets. The findings reveal that cryptocurrency can be considered a valid form of property (al-māl) to be used as dowry, provided that it has clear value, can be transferred, and is mutually agreed upon by both parties. The DSN-MUI fatwa permits crypto as a commodity or investment instrument but prohibits its use as currency. Therefore, using cryptocurrency as dowry is legally acceptable in both Islamic and national law, as long as it adheres to sharia principles, transparency, and lawful intentions.